TOR as a Regulatory Target in Rhipicephalus microplus Embryogenesis - Waltero, Camila; de Abreu, Leonardo Araujo; Alonso, Thayná; Nunes-da-Fonseca, Rodrigo; da Silva Vaz, Itabajara; Logullo, Carlos (Frontiers in Physiology, 2019)
Embryogenesis is a metabolically intensive process carried out under tightly controlled conditions. The insulin signaling pathway regulates glucose homeostasis and is essential for reproduction in metazoan model species. Three key targets are part of this signaling pathway: protein kinase B (PKB, or AKT), glycogen synthase kinase 3 (GSK-3), and target of rapamycin (TOR). While the role of AKT and GSK-3 has been investigated during tick embryonic development, the role of TOR remains unknown. In this study, TOR and two other downstream effectors, namely S6 kinase (S6K) and eukaryotic translation initiation factor 4E-binding protein 1 (4E-BP1), were investigated in in vitro studies using the tick embryonic cell line BME26. First, we show that exogenous insulin can stimulate TOR transcription. Second, TOR chemical inhibition led to a decrease in BME26 cell viability, loss of membrane integrity, and downregulation of S6K and 4E-BP1 transcription. Conversely, treating BME26 cells with chemical inhibitors of AKT or GSK-3 did not affect S6K and 4E-BP1 transcription, showing that TOR is specifically required to activate its downstream targets. To address the role of TOR in tick reproduction, in vivo studies were performed. Analysis of relative transcription during different stages of tick embryonic development showed different levels of transcription for TOR, and a maternal deposition of S6K and 4E-BP1 transcripts. Injection of TOR double-stranded RNA (dsRNA) into partially fed females led to a slight delay in oviposition, an atypical egg external morphology, decreased vitellin content in eggs, and decreased larval hatching. Taken together, our data show that the TOR signaling pathway is important for tick reproduction, that TOR acts as a regulatory target in Rhipicephalus microplus embryogenesis and represents a promising target for the development of compounds for tick control.